John Bastin 1929–2018. Issue 2 (1st April 2018) - Ade, Peter; Clegg, Peter; Robson, Ian
Abstract : The pioneer of UK ground-based submillimetre astronomy is remembered by Peter Ade, Peter Clegg and Ian Robson .